High Order QCD Predictions for Inclusive Production of W Bosons in pp Collisions at s=13 TeV - Hasan Ogul; Kamuran Dilsiz; Emrah Tiras; Ping Tan; Yasar Onel; Jane Nachtman (Advances in High Energy Physics)
Predictions of fiducial cross sections, differential cross sections, and lepton charge asymmetry are presented for the production of W± bosons with leptonic decay up to next-to-next-to-leading order (NNLO) in perturbative QCD. Differential cross sections of W± bosons and W boson lepton charge asymmetry are computed as a function of lepton pseudorapidity for a defined fiducial region in pp collisions at s=13 TeV. Numerical results of fiducial W± cross section predictions are presented with the latest modern PDF models at next-to-leading order (NLO) and NNLO. It is found that the CT14 and NNPDF 3.0 predictions with NNLO QCD corrections are about 4% higher than the NLO CT14 and NNPDF 3.0 predictions while MMHT 2014 predictions with NLO QCD corrections are smaller than its NNLO QCD predictions by approximately 6%. In addition, the NNLO QCD corrections reduce the scale variation uncertainty on the cross section by a factor of 3.5. The prediction of central values and considered uncertainties are obtained using FEWZ 3.1 program.